An Atmospherics of the City : Baudelaire and the Poetics of Noise - Chambers, Ross (Book collections on Project MUSE., 2015)
"An Atmospherics of the City traces Charles Baudelaire's evolution from a writer who practices a form of fetishizing aesthetics in which poetry works to beautify the ordinary to one who perceives background noise and disorder--the city's version of a transcendent atmosphere--as evidence of the malign work of a transcendent god of time, history, and ultimate destruction"--